Contextualizing systemic risk - Lukas Scheffknecht (Research On Money in the Economy (ROME), 2013)
I analyze the rapidly growing literature about systemic risk in financial markets and find an important commonality. Systemic risk is regarded to be an endogenous outcome of interactions by rational agents on imperfect markets. Market imperfections give rise to systemic externalities which cause an excessive level of systemic risk. This creates a scope for welfare-increasing government interventions. Current policy debates usually refer to them as 'macroprudential regulation'. I argue that efforts undertaken in this direction - most notably the incipient implementation of Basel III- are insufficient. The problem of endogenous financial instability and excessive systemic risk remains an unresolved issue which carries unpleasant implications for central bankers. In particular, monetary policy is in danger of persistently getting burdened with the difficult task to simultaneously ensure macroeconomic and financial stability.
Keywords: E44; E52; G01; G18; 330; Systemic Risk; Systemic Externalities; Macroprudential Regulation; Basel III